The Characteristics Of Inhabitants Palu Rivers Flood Basin - Pudji Astutiek Fachruddin (JURNAL RUANG / ISSN : 2085-6962, 2010)
The Aims of the study was to analyze the impact of urban economic activities, socio-economic conditions and sociocultural of migrants on the development of housing in the Palu Rivers flood Basin. The Data were obtained through quistionare, interview, observation, and documentation. The number of sample was 15 % of 150 respondents. The Method of Analysis used in the study was descriptive – qualitative. Result of the study indicates that socio-economic activities have an effect on the characteristic of the inhabitants. This is indicate by 82 % of the respondents come to Palu to find a job and 47,67 % live in the working location, and 24,66 % live around it. Relationship between the people who come from the same village residing in the area is 57,33 %. The specific characteristic of the residents found in the location is they work in informal sector of town. Therefore it is recommended to the government to make a policy to organize the housing in the area based on environmental law and the characteristic of the inhabitants.It also recommended to place free area about 50 metre – 100 metre from the housing, so that it can be used as a flood barrier as well as green area.